An investigation of packet scheduling algorithms for long term evolution-advanced - Mohd. Ramli, Huda Adibah; Hasan, Mohamad Kamrul; Ismail, Ahmad Fadzil; Hassan Abdalla Hashim, Aisha; Abdullah, Khaizuran (IEEE, 2012)
Carrier Aggregation (CA) is a potential technique to increase the band width in LTE-Advanced system. However, the introduction of CA brings a number challenges to the traditional Radio Resource Management (RRM) mechanisms. This paper investigates the current algorithms of CA and packet scheduling forthe Long Term Evolution-Advanced (LTE-A). In the beginning, the evolution from third generation (3G) to fourth generation (4G) is illustrated in terms of featured performance requirements and the integration of current and future radio access technologies, is also highlighted. Additionally, this paper discusses the current technical trends and possible improvements of the packet scheduling algorithms with CA for LTE-A.